SPHERICAL TANK LEVEL CONTROL SYSTEM USING CONVENTIONAL & INTELLIGENT CONTROL STRATEGIES - Sudha, R.; Manohar, Gunaselvi; Stanley, Pearley; R, Lakshmi; V, Sunanthini (International Journal of Psychosocial Rehabilitation, 2019)
The process industry frontages the problem of controlling the process parameters, which is considered as the most critical problem in the industrial scenario. Hence, in this paper, the liquid level control in spherical tank is considered as the control parameter. In spherical tank, the area of cross section of the tank varies nonlinear as the height of the tank changes, which changes the shape of the liquid level in a nonlinear manner in the spherical tank. Level control of this nonlinear process is done using conventional (PI) and intelligent controllers (fuzzy & neural). Here the performance of each type of controller is evaluated using the time integral criteria. The process was modelled by deriving the mathematical model and further steps were implemented in matlab and labview out of the different controllers used, fuzzy controller outperforms PI and neural controllers in terms of smooth response to servo and regulatory changes and produces lower values of performance indices.